Disruption of Routine Behaviors Following the Deepwater Horizon Oil Spill. Issue 3 (4th March 2018) - Parks, Vanessa; Drakeford, Leah; Cope, Michael R.; Slack, Tim
ABSTRACT: This paper frames the unfolding impacts of the Deepwater Horizon oil spill as a process of lifeway disruption, analyzing the degree to which residents of spill affected communities were prevented from undertaking routine behaviors during the disaster. Special attention is paid to the influence of time, natural resource employment, and community sentiment. Drawing on data from the Louisiana Community Oil Spill Survey, the results show that people in the spill impacted region were prevented from engaging in routine behaviors, though this disruption has steadily decreased over time, suggesting a general trend toward recovery. Consistent with the renewable resource community concept, the results also show that those with ties to the fishing industry were more likely to be prevented from undertaking routine behaviors than were nonfishers. Finally, community sentiment is shown to ameliorate routine behavior disruption, thus, promoting resilience. Overall, these results challenge notions of monolithic paths to disaster recovery.